2020
DOI: 10.21203/rs.3.rs-33859/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Akkermansia Muciniphila and Environmental Enrichment Reverse Cognitive Impairment Associated With High-fat High-cholesterol Consumption Through the Gut-brain Axis

Abstract: Background: Non-alcoholic steatohepatitis (NASH) is one of the most prevalent diseases worldwide. A high-fat, high-cholesterol (HFHC) diet leads to an early NASH model. It has been suggested that gut microbiota mediates the effects of diet through the microbiota-gut-brain axis, modifying the host’s brain metabolism and disrupting cognition.Results: Here, we target NASH-induced cognitive damage by testing the impact of environmental enrichment (EE) and the administration of either Lacticaseibacillus rhamnosus G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…For instance, physical exercise is an important EE component capable of modulating brain plasticity (van Praag et al, 2000); however, it cannot explain the full ocular dominance plasticity enhancement observed in EE rodents (Baroncelli et al, 2012). Some studies demonstrated changes in the microbiota composition and diversity of rodents after physical exercise, and an increase in the Bacteroidetes phylum and the Lachnospiraceae family (Evans et al, 2014;Mika et al, 2015), and recently EE has been shown to modulate the gut microbiota composition in adult rats (Higarza et al, 2021). Changes in bacteria families after diet or physical exercise were also correlated to behavioral alterations.…”
Section: Article Llmentioning
confidence: 99%
“…For instance, physical exercise is an important EE component capable of modulating brain plasticity (van Praag et al, 2000); however, it cannot explain the full ocular dominance plasticity enhancement observed in EE rodents (Baroncelli et al, 2012). Some studies demonstrated changes in the microbiota composition and diversity of rodents after physical exercise, and an increase in the Bacteroidetes phylum and the Lachnospiraceae family (Evans et al, 2014;Mika et al, 2015), and recently EE has been shown to modulate the gut microbiota composition in adult rats (Higarza et al, 2021). Changes in bacteria families after diet or physical exercise were also correlated to behavioral alterations.…”
Section: Article Llmentioning
confidence: 99%
“…Strikingly, in this study, the microbiota of the HSPEN group was extremely abundant with Akkermansia species (Figure 4C). Previous studies have indicated that Akkermansia may be regulated by bile acids and increased levels of bile acids can reduce the population of Akkermansia in mice (Higarza et al, 2021;Keshavarz Azizi Raftar et al, 2021). This finding seems to be in contradiction with the acknowledged enrichment of probiotic species within this genus.…”
Section: Discussionmentioning
confidence: 80%